Anxiety and Violence Against Nurses in Turkey During The COVID-19 Pandemic - Sevilay Senol Celik; Hulya Bulut; Azize Atali Ozbas; Azize Karahan; Gulten Koc; Cigdem Ozdemir Ozleyen; Firuze Cevik Aydin; Beyhan Celik; İnci Mercan Annak; Yusuf Celik (KHD-Production, 2023)
During the pandemic process, nurses felt more anxious and nervous compared to other health professionals and were frequently exposed to verbal-emotional-psychological violence. This study was conducted to determine the anxiety levels of nurses, their exposure to violence, and the factors affecting the anxiety and witnessed violence of nurses during the COVID-19 pandemic in Turkey. The descriptive study data were collected in the period between October 2020 and March 2021 via the online questionnaire published on the Turkish Nurses Association’s website. The study sample consisted of 3,230 nurses. In this study, it was found that the majority of participants in the study were women (83,5%), working 24-hour shifts (49.3%) at hospitals run by the Ministry of Health (68.7%), caring for COVID-19 patients (82.1%). Nurses experienced very high levels of anxiety and were exposed to violence from patients, family members, or other healthcare professionals during the COVID-19 pandemic. Also, this study shows that nurses experienced high anxiety levels and increased exposure to violence in association with the high number of patients to provide care for, long working hours, being forced to work despite COVID-19 symptoms, working with COVID-19 patients, the fear of infecting family members, having difficulties in caring for family members, financial losses, and the unavailability of changing rooms. In line with the results of this study, the responsibility range of managers and decision-makers is wide in protecting the physical and mental integrity of nurses, anticipating, and addressing their needs and resolving their problems, and managing the nurse manpower and the supply of PPE in accordance with standards so that nurses can provide qualified and safe nursing practices. The findings of this study will help to ensure that nursing care is safe, consistent, and competent, as well as guide future planning.